2022
DOI: 10.1101/2022.05.30.493980
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reported Health Benefits of a Vegan Dog Food – A Likert Scale-type Survey of 100 Guardians

Abstract: Introduction There has been a surge in feeding plant-based foods to pets and advocates extol the health benefits of this practice. However, there is a lack of scientific evidence to support health claims for vegan diets in dogs. Aims This study aimed to quantify perceived health changes by dog guardians following the feeding of a single brand of UK-produced vegan food for a period of 3 to 12 months. Methods Dog guardians registered as feeding the vegan food for 3 - 12 months were invited to participate in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Regarding health and palatability, while there are numerous methodological limitations with the existing literature, the latest systematic review found that plant-based pet foods are comparable, or perhaps slightly more advantageous, for the health of pet dogs and cats (Domínguez-Oliva et al, 2023). However, a cautious approach is warranted, as further validation and controlled clinical trials are required (Davies, 2022). Important uncertainties remain, but the same is more true for insect diets; data on the nutritional quality of insects is less well-documented, with limited available data (Bosch et al, 2014;McCusker et al, 2014;Mouithys-Mickalad et al, 2020;Acuff et al, 2021).…”
Section: Pet Food: Environmental Impacts Of Insects Compared To Conve...mentioning
confidence: 99%
“…Regarding health and palatability, while there are numerous methodological limitations with the existing literature, the latest systematic review found that plant-based pet foods are comparable, or perhaps slightly more advantageous, for the health of pet dogs and cats (Domínguez-Oliva et al, 2023). However, a cautious approach is warranted, as further validation and controlled clinical trials are required (Davies, 2022). Important uncertainties remain, but the same is more true for insect diets; data on the nutritional quality of insects is less well-documented, with limited available data (Bosch et al, 2014;McCusker et al, 2014;Mouithys-Mickalad et al, 2020;Acuff et al, 2021).…”
Section: Pet Food: Environmental Impacts Of Insects Compared To Conve...mentioning
confidence: 99%